KONSEP CULPA DALAM PERKARA PIDANA SUATU ANALISIS PERBANDINGAN PUTUSAN NOMOR 18/Pid.B/2017/PN.TOBELO - Ernest Sengi (Faculty of Law - Tarumanagara University, 2019)
The concept of omission or culpa from the legal aspect is very different from the concept of omission or culpa that is understood everyday. Many events include omission or culpa but the incident may not be a criminal act. Thus, law enforcement must be careful in giving meaning to a legal act related to omission. Court Decision Number 18 / Pid.B / 2017 / PN.TOb. is a decision which is the object of research in this paper, in which the author disagrees about the concept of omission or culpa which is considered by the Tobelo District Court judge in that decision, although I agrees that the defendant's actions were omission. The analysis used is legal analysis using a statute approach and case approach so that it can find out the basis of the court's consideration of choosing Pasal 359 KUHP dropped against the defendant Imsal Ilahi Baksi. In its consideration, it was found that Tobelo District Court judges interpreted omission as